Machinability of Ni-rich NiTiHf high temperature shape memory alloy - (:unkn) unknown (IOP PUBLISHING LTD, 2019)
Machining of Ni-rich Ni50.3Ti29.7Hf20 (at%) high temperature shape memory alloys was evaluated under flood cooling conditions. Effects of various cutting speeds (between 20 and 120 m min(-1)), depth of cuts (between 0.4 and 1 mm), and the associated cutting forces on the work-piece surface quality and tool wear of this alloy are presented. Experimental data demonstrates that abrasion and adhesion were the predominant wear mechanisms leading to extreme wear in a short machining time. Thermal softening mechanism dominated the trend of cutting forces until 95 m min(-)1 cutting speed. Beyond this speed, force components sharply increased resulting from extreme tool wear. Chip breakability of this alloy is much better when compared to NiTi shape memory alloy.
Keywords: NiTiHf shape memory alloy; machinability; tool wear; force components; TOOL-WEAR; CHIP FORMATION; DRY; PERFORMANCE; MICROSTRUCTURE; OPTIMIZATION; DEFORMATION; MECHANISM; BEHAVIOR; PHASE